“Believe me, only I know how I feel.” An autoethnographic account of experiences of epistemic injustice in mental health care - Hultman, Lill; Hultman, Maya (Frontiers in Psychiatry, 2023)
In Sweden, support and service for people with disabilities is provided under the Swedish disability legislation, which has a clear focus on the individual’s right to a life like that of any other citizen and on promoting equality and participation in society. Nevertheless, having a physical impairment makes it clear that equal mental health care is not provided in practice. This becomes particularly salient when there is a need for mental health in-patient care. In this article, the aim is to explore our own experiences of epistemic injustice in relation to mental health care provision in a situation where one of us has a mobility impairment that require the presence of personal assistants in everyday life. Critical personal narrative is applied to highlight the different, but intertwined experiences of a young female mental health user with a physical disability and her mother. Diary entrances, shared discussions and extracts from health care records are used to illustrate how epistemic injustice may occur in health care practices. In the analysis, we use Fricker’s concepts that relate to different aspects of epistemic injustice, to show how power is exerted. Healthcare professionals’ inability to value and integrate patients experience-based knowledge into practice where the lack of a holistic perspective visualizes what happens when people do not fit into predefined categories. Instead of strengthening patients’ rights, health care professionals discredit patients’ and family members knowledge, and thereby giving themselves epistemic privilege. People with the combined experience of both disabilities and mental health issues are vulnerable to epistemic injustice and epistemic harm since they are commonly denied both epistemic credibility and authority. Our results highlight the importance of counteracting resilient structures of social privilege and power and identifying and, in as far as possible, removing the mechanisms that exclude the epistemic resources of people with disabilities and their family members from being part of shared epistemic resources.